Development of multiple choice question bank in otorhinolaryngology by item analysis: a cross-sectional study - Khilnani, Ajeet Kumar; Thaddanee, Rekha; Khilnani, Gurudas (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: Multiple choice questions (MCQs) are routinely used for formative and summative assessment in medical education. Item analysis is a process of post validation of MCQ tests, whereby items are analyzed for difficulty index, discrimination index and distractor efficiency, to obtain a range of items of varying difficulty and discrimination indices. This study was done to understand the process of item analysis and analyze MCQ test so that a valid and reliable MCQ bank in otorhinolaryngology is developed. Methods: 158 students of 7th Semester were given an 8 item MCQ test. Based on the marks achieved, the high achievers (top 33%, 52 students) and low achievers (bottom 33%, 52 students) were included in the study. The responses were tabulated in Microsoft Excel Sheet and analyzed for difficulty index, discrimination index and distractor efficiency. Results: The mean (SD) difficulty index (Diff-I) of 8 item test was 61.41% (11.81%). 5 items had a very good difficulty index (41% to 60%), while 3 items were easy (Diff-I >60%). There was no item with Diff-I <30%, i.e. a difficult item, in this test. The mean (SD) discrimination index (DI) of the test was 0.48 (0.15), and all items had very good discrimination indices of more than 0.25. Out of 24 distractors, 6 (25%) were non-functional distractors (NFDs). The mean (SD) distractor efficiency (DE) of the test was 74.62% (23.79%). Conclusions: Item analysis should be an integral and regular activity in each department so that a valid and reliable MCQ question bank is developed.